Trailing the Growth from Nativism to Africanity in Lusophone African Poetry - Sovon Sanyal (Bina Nusantara University, 2010)
Article explored the development of African poetry, that is from nativism to be Africanity, in Lusophone African poetries. The study used library research by analysing the impact of printing press, public education, and freedom of expression emergences toward literary activities in Portuguese colonies in Africa. In this regard ethnological and historical studies on the colonies had an important role to play for the later development of nationalism among the colonised African peoples. Article’s discussion concerned with describing proper literary activities in Portuguese began in the Lusophone countries of Africa, poetry characterization by the “black” and “white” presentations, added by some example of poetries. It can be concluded the problematic of colour is present in African poems in Portuguese right from its inception, The common purpose of the nineteenth century Lusophone African poets was to discover the regional cultural history and identity, which was denied to them for centuries by the foreign rulers.